Colorectal adenomas and diabetes: implications for disease prevention. (July 2015) - Steele, R. J. C.; Anderson, A. S.; Macleod, M.; Craigie, A. M.; Caswell, S.; Belch, J.; Treweek, S.; on behalf of the BeWEL team
Abstract Aim This study assessed the baseline type II diabetes mellitus (T2DM) risk status among overweight patients with screen‐detected colorectal adenomas and explored the implications of the findings for preventative practice. Method Participants aged between 50 and 74 years (73% of whom were men) were recruited from four Scottish health boards and assessed for diabetes risk. Participants were categorized as at 'high' diabetes risk if glycated haemoglobin (HbA1c) was between 6.0 and 6.4% or fasting plasma glucose (FPG) was between 5.5 and 6.9 mmol/l and as potentially undiagnosed T2DM when HbA1c ≥ 6.5% or FPG ≥ 7 mmol/l. Secondary outcome measures included anthropometric measurements, blood pressure and the plasma lipid profile. The tests were repeated at 12 months and diabetes risk categories were reassessed following intervention procedures. Results Forty‐seven (14.3%) of the 329 participants had a preexisting diagnosis of T2DM. Of the remainder with complete biochemistry results (n = 250), 19 (7.6%) were classified as having potentially undiagnosed T2DM and 125 (50.0%) as being at high risk of developing diabetes. More than a quarter of participants in all categories had raised waist circumference, hypertension and plasma lipids, indicative of raised cardiovascular risk. At 12 months' follow‐up, the diabetes risk category diminished in 20% of the intervention group vs 11% in the controls [OR 2.26 (95% CI 1.03–4.96)]. Conclusion Our results suggest that a diagnosis of adenoma in overweight patients provides a health service opportunity for diabetes assessment, prevention and management in a high‐risk population at a potentially teachable moment.